2022
DOI: 10.1159/000522280
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Glucose Tolerance and Its Change on Incident Proteinuria: Analysis of a Nationwide Population-Based Dataset

Abstract: <b><i>Introduction:</i></b> Although diabetes mellitus (DM) increases the risk of proteinuria, the relationship between prediabetes and proteinuria remains not fully understood. Further, whether the change in glucose is associated with the risk for proteinuria is unknown. <b><i>Methods:</i></b> This was a retrospective cohort study that included 1,849,074 participants (median age, 45 years; 59.3% men). No participants were taking glucose-lowering medications, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Similarly, Vieira et al ( 17 ), in a post hoc analysis of SPRINT trial among 9361 participants (aged ≥50 years) without diabetes, found that IFG at baseline was not associated with worsening of kidney function or albuminuria; moreover, no subsequent effect modification according to age was observed. Suzuki et al ( 54 ), among 1 849 074 participants, showed that prediabetes (as defined by HbA1c levels of 5.7–6.4%) increased the risk of proteinuria among both participants aged < 50 and those 50 years or older.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Vieira et al ( 17 ), in a post hoc analysis of SPRINT trial among 9361 participants (aged ≥50 years) without diabetes, found that IFG at baseline was not associated with worsening of kidney function or albuminuria; moreover, no subsequent effect modification according to age was observed. Suzuki et al ( 54 ), among 1 849 074 participants, showed that prediabetes (as defined by HbA1c levels of 5.7–6.4%) increased the risk of proteinuria among both participants aged < 50 and those 50 years or older.…”
Section: Discussionmentioning
confidence: 99%
“…First, we performed multiple imputations for missing data based on the assumption of missing data at random, as previously described. 11,12) HRs and standard errors were calculated using Rubin's rules. Second, death may be a competing risk factor for CVD events.…”
Section: Methodsmentioning
confidence: 99%
“…The results were aggregated over 20 imputed sets using Rubin's rules. 20 , 21 Second, we used the Fine and Gray subdistribution hazard model to examine the association between cancer history and the incidence of hypertension because all-cause death could be considered a competing risk factor. Third, we excluded individuals with a diagnosis of hypertension based only on ICD-10 codes in the primary analysis.…”
Section: Methodsmentioning
confidence: 99%